Taekwondo for Visually Impaired Individuals. (Fiep Bulletin - online, 2013)
The present study aims at developing Taekwondo techniques for visually impaired individuals. The study intends to show that individuals who are visually impaired are able to learn and develop the required skills to practice Taekwondo. As those individuals suffer from physical, psychological and social limitations, the practice of any physical activity is essential for them, and by practicing Taekwondo, they are allowed to be in contact with one more sport. The study used as its parameter the studies already developed by researchers in the area of deficiency and their suggestions on how to deal with those deficiencies. The research was approved by the Committee of Ethics of the “Centro Universitário do Planalto de Araxá MG. The field research was developed with three visually impaired individuals. They were given all the information referring to the initiation to Taekwondo, and at the end of the study they would be evaluated as for the progress in the stripe. The students attended classes for six months, two hours twice a week. In the classes the instructors worked with their basic motor skills, physical and mental development, concentration, self-confidence, and the basic moves of Taekwondo. At the end of the process, the students were evaluated. In the exam. Their readiness was checked to see the possibility for them to move on to new techniques or if they would be kept longer in the same level. The students made a presentation following basic requirements and were approved with letter A, being automatically placed on the 8th Gub yellow stripe. During that period it was noticed a strong desire those individuals have to live and learn. In this sense, their deficiency does not prevent them from living their lives intensively and what is most significant they really want to live and live with joy, regardless their condition. KEY
Keywords: Visual imparity; Taekwondo; Araxá